54.8k views
0 votes
Simplify 63x83-(6-4)=

User Dnhyde
by
5.3k points

2 Answers

0 votes

The answer would be 5227. If you subtract what is in parenthesis first and then multiply it that should be your answer.

User Pablo Fonseca
by
5.5k points
7 votes

Answer:
5,227

Explanation:

Given the expression
63*83-(6-4) you can simplify it by applying these steps:

First, make the subtraction of the numbers that are inside of the parentheses:


=63*83-(2)

Apply multiplication of signs to eliminate the parentheses. Remember that:


(-)(-)=+\\(+)(+)=+\\(-)(+)=-

Then:


=63*83-2

Now, make the multplication indicated:


=5,229-2

Finally, subtract both numbers:


=5,227

User Emre Tekince
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.